STUDI KASUS PEMBELAJARAN TEMATIK DI SD KELAS AWAL PADA PROGRAM KAMPUS MENGAJAR - Siti Nuriya; Wahju Dyah Laksmi Wardhani; Shella Az Zahro (Universitas Muhammadiyah Surabaya, 2022)
This article aims to narrate the point of view from experiences undergraduate students' in PG PAUD in designing learning activities in Indonesian subjects by applying a thematic approach.Â The development of learning in early grade elementary schools using Curriculum 13 designed with a thematic approach as a corridor for existing subjects, including learning Indonesian.Â The application of thematic learning in SD which has different from the implementation in PAUD that understands thematic development as a corridor for stimulating aspects of child development, while in SD thematic development is directed at strengthening concepts according to subjects aimed at training and developing basic competencies in the realm of attitudes, knowledge and skills.Â By using a case study approach, this research uses a narrative analysis technique to describe the uniqueness of the difference in the reality of the application of thematic learning in early grade elementary schools with the theoretical understanding of students with early childhood education backgrounds.Â Keywords: Teaching Campus; Early Grade Elementary School; Thematic